Cone dystrophy and ectopic synaptogenesis in a Cacna1f loss of function model of congenital stationary night blindness (CSNB2A). Issue 1 (1st January 2018) - Waldner, D. M.; Giraldo Sierra, N. C.; Bonfield, S.; Nguyen, L.; Dimopoulos, I. S.; Sauvé, Y.; Stell, W. K.; Bech-Hansen, N. T.
ABSTRACT: Congenital stationary night blindness 2A (CSNB2A) is an X-linked retinal disorder, characterized by phenotypically variable signs and symptoms of impaired vision. CSNB2A is due to mutations in CACNA1F, which codes for the pore-forming α1F subunit of a L-type voltage-gated calcium channel, Cav 1.4. Mouse models of CSNB2A, used for characterizing the effects of various Cacna1f mutations, have revealed greater severity of defects than in human CSNB2A. Specifically, Cacna1f -knockout mice show an apparent lack of visual function, gradual retinal degeneration, and disruption of photoreceptor synaptic terminals. Several reports have also noted cone-specific disruptions, including axonal abnormalities, dystrophy, and cell death. We have explored further the involvement of cones in our 'G305X' mouse model of CSNB2A, which has a premature truncation, loss-of-function mutation in Cacna1f . We show that the expression of genes for several phototransduction-related cone markers is down-regulated, while that of several cellular stress- and damage-related markers is up-regulated; and that cone photoreceptor structure and photopic visual function – measured by immunohistochemistry, optokinetic response and electroretinography – deteriorate progressively with age. We also find that dystrophic cone axons establish synapse-like contacts with rod bipolar cell dendrites, which they normally do not contact in wild-type retinas – ectopically, among rod cell bodies in the outer nuclear layer. These data support a role for Cav 1.4 in cone synaptic development, cell viability, and synaptic transmission of cone-dependent visual signals. Although our novel finding of cone-to-rod-bipolar cell contacts in this mouse model of a retinal channelopathy may challenge current views of the role of Cav 1.4 in photopic vision, it also suggests a potential new target for restorative therapy.